Analisis Loyalitas Karyawan terhadap Produktivitas Kerja - Hani Siti Hanifah (Jurnal Inovasi Bisnis dan Kewirausahaan, 2019)
Using a descriptive and verification approach, the present study looks at employee loyalty and how it affects work productivity. 76 out 324 employees at a garment company in Garut, Indonesia, selected using Slovin’s formula. Data analysis was performed using simple linear regression analysis. The results t-Test revealed that employee loyalty had a significant positive effect on work productivity with an observed value of 2.796, higher than the critical t of 1.67. This finding leads to a conclusion that the more loyal an employee is, the more productive he is.